2017
DOI: 10.29252/nrip.irj.15.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Happiness of Male Adolescents With Disabled Physical Mobility: Benefits of Mental Rehabilitation Based on Positive Thinking Skills Training

Abstract: Objectives:The main purpose of this research was to study the effectiveness of positive thinking skills training on increasing happiness of male adolescents with physical-mobility disability. Methods:In this study an experimental research design with pre-test, post-test, and control group is used. All adolescents (boys) having disabled physical mobility from all the high schools in southern parts of Tehran in the year 2012-2103 were our statistical community. Among them, 16 students were selected by two-stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Khodadadi Sangdeh, Toulaian, and Balqanabadi (2014) in their studies concluded that positive psychotherapy can affect the happiness of mothers of children with special needs. Rostami, Younesi, Movaleli, Farhoud, and Biglarian (2014) also found that training positive thinking skills will enhance the happiness of adolescents with hearing loss. Hariri and Khodami (2011) in a study on the use of teaching positive thinking and happiness to the elderly in Tehran found that this training could significantly increase their hope and improve their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Khodadadi Sangdeh, Toulaian, and Balqanabadi (2014) in their studies concluded that positive psychotherapy can affect the happiness of mothers of children with special needs. Rostami, Younesi, Movaleli, Farhoud, and Biglarian (2014) also found that training positive thinking skills will enhance the happiness of adolescents with hearing loss. Hariri and Khodami (2011) in a study on the use of teaching positive thinking and happiness to the elderly in Tehran found that this training could significantly increase their hope and improve their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…) (Shokhmgar, 2017). (Peterson et al, 2007) (Khramtsova, 2008) (Wong, 2012) (Ramesh et al, 2013) (Moaser, 2016) (Panahi et al, 2016) (Rostami et al,2017).…”
mentioning
confidence: 99%